The Role of Institutions and Networks in Firms' Offshoring Decisions - Simone Moriconi; Giovanni Peri; Dario Pozzoli (Copenhagen Business School (CBS), Department of Economics, 2018)
The offshoring of production by multinational firms has expanded dramatically in recent decades, increasing the potential for economic growth and technological transfers. What determines the location of such offshore production? How do the policies and characteristics of countries affect these decisions? Do firms choose specific countries because of their policies or because they are more familiar with them? In this paper, we use a very rich dataset on Danish firms to analyze how their decisions regarding offshore production depend on institutional characteristics and firm-specific bilateral connections with these countries. We find that institutions that enhance investor protections and reduce corruption increase the probability of offshoring, while those that introduce regulatory constraints in the labor market discourage it. We also show that offshoring activities are more likely for firms that have developed networks in the country of destination.
hdl:10398/9658
Keywords: F16; J24; J38; 330; Offshoring; product market; labor regulations; network; fixed costs